PENGARUH MODEL PEMBELAJARAN BAMBOO DANCING TERHADAP HASIL BELAJAR PADA MATA PELAJARAN IPA SISWA KELAS VI SDN 11 NANGA PINOH - Lia Kastia; Rachmat Sahputra; Eko Fery Haryadi Saputra (JURNAL PENDIDIKAN DASAR, 2018)
Abstract: This study aims to see the significance effect of bamboo dancing learning model on learning outcomes in natural science subjects (IPA). The location of this research is at State Elementary School No. 11 Nanga Pinoh. The location of this research is at State Elementary School No. 11 Nanga Pinoh. This type of research is a pre-experiment research with one-group pretest-posttest design. The population of this research is the students of class VI SDN 11 Nanga Pinoh academic year 2017/2018. The sample was obtained by class VI with 29 students. The data analysis technique used is t-test. The result of this research shows that the influence of bamboo dancing learning model on the result of study on the subject of Natural Science (IPA) obtained by t-test calculation is obtained tcount = 3,75 table = 2,10. based on the results of data analysis obtained conclusion from pretest value before applied bamboo dancing learning model that is with average 60,46 and posttest value after applied bamboo dancing learning model that is with average 77,47. meaning the results of this study indicate that the influence of bamboo dancing learning model has a significant effect on the results of learning, especially on subjects of Natural Sciences (IPA). Based on the data analysis of N-Gain High category score of 6 students, medium category as many as 16 students, and low category as many as 7 students. Keywords: Bamboo Dancing Learning Model, Science learning out comesn Nature (Science Learning) Abstrak: Penelitian ini bertujuan Mengetahui hasil belajar siswa pada mata pelajaran IPA di kelas VI SDN 11 Nanga Pinoh sebelum dan sesudah menggunakan model pembelajaran Bamboo Dancing. Tempat pelaksanaan penelitian ini adalah di Sekolah Dasar Negeri No. 11 Nanga Pinoh. Jenis penelitian ini adalah penelitian pre-eksperimen dengan design one-group pretest-posttest. Populasi penelitian ini adalah siswa kelas VI SDN 11 Nanga Pinoh tahun ajaran 2017/2018. Sampel diperoleh kelas VI dengan jumlah 29 siswa. Teknik analisis data yang digunakan adalah menggunakan uji-t. Hasil penelitian menunjukkan pengaruh signifikan pengaruh model pembelajaran bamboo dancing terhadap hasil belajar pada mata pelajaran Ilmu Pengetahuan Alam (IPA) yang diperoleh hasil perhitungan uji-t diperoleh thitung = 3,75 ttabel = 2,10. berdasarkan hasil analisis data diperoleh kesimpulan dari nilai pretest sebelum diterapkan model pembelajaran bamboo dancing yaitu dengan rata-rata 60,46 dan nilai posttest sesudah diterapkan model pembelajaran bamboo dancing yaitu dengan rata-rata 77,47. artinya hasil penelitian ini menunjukkan bahwa pengaruh model pembelajaran bamboo dancing ini berpengaruh signifikan terhadap hasil belajar khususnya pada mata pelajaran Ilmu Pengetahuan Alam (IPA). Berdasarkan analisis data hasil nilai N-Gain kategori Tinggi sebanyak 6 siswa, kategori sedang sebanyak 16 siswa, dan kategori rendah sebanyak 7 siswa. Kata Kunci: Model Pembelajaran Bamboo Dancing, hasil belajar Ilmu Pengetahuan Alam (IPA).